2001
DOI: 10.1017/s0953756201003938
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of intracellular peptidase and proteinase activities from the mycelium of a cord-forming wood decay fungus, Serpula lacrymans

Abstract: Serpula lacrymans is a basidiomycete cord-forming wood decay fungus which reallocates nitrogen within an extensive perennial mycelial system in response to spatial discontinuities in external nutrient supply. Intracellular stored protein is mobilised by conversion to amino acids at nutrient-poor sites within a mycelium or when a whole mycelium is starved. Intracellular peptidase and proteinase activities of the mycelium were investigated with the aim of identifying proteases specifically activated in response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
(15 reference statements)
0
8
0
Order By: Relevance
“…There is good evidence that breakdown of material for reuse in other mycelial parts occurs within intact cell membranes (Lilly et al, 1991;Watkinson et al, 2001) and thus resembles apoptosis in animal cells (Olsson, 2001). Searches for homologues of Fig.…”
Section: Discussionmentioning
confidence: 99%
“…There is good evidence that breakdown of material for reuse in other mycelial parts occurs within intact cell membranes (Lilly et al, 1991;Watkinson et al, 2001) and thus resembles apoptosis in animal cells (Olsson, 2001). Searches for homologues of Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Starvation-induced proteinases have been investigated with a view to developing a suitable reporter for identifying sites in the mycelium where autolysis and regression are induced. A serine proteinase activity was identified in Serpula lacrymans with characteristics consistent with a role in mobilizing intracellular protein stores from cytoplasm, as well as a lysosomal-type activity optimal at low pH (Watkinson et al, 2001;Wadekar et al, 1995). Genes for serine proteinases of several cord-forming wood decay fungi have been cloned (Eastwood & Tlalka, unpublished; Eastwood & Higgins, unpublished) and show homology to other fungal serine proteinases with putative roles in internal protein mobilization (Kingsnorth et al, 2001).…”
Section: Development and Function Of Translocating Networkmentioning
confidence: 99%
“…lacrymans commonly associated with the built environment. We hypothesize that responses to nitrogen status, including cord development, and the induction of an intracellular lysosomal-type proteinase activity (Watkinson et al, 2001) not found in other fungi investigated, might be mediated through changes in intracellular amino acid. Scavenging mycelium colonizes a new wood food source, inducing variegatic acid (VA) production, and expression of oxidoreductase enzymes which drive hydroxyl radical attack on the lignocellulose composite.…”
Section: Future Directionsmentioning
confidence: 86%